Monitoring of Productivity and Crop Water Stress in Pearl millet using the SPAW Model - Rao, A S; Joshi, N L; Saxton, K E (Annals of Arid Zone, 2016)
For assessment of soil water in the Indian arid zone, the profile soil moisture content in pearl millet, grown under optimum moisture and rainfed conditions at Jodhpur, was simulated using the SPAW (Soil-Plant-Air- Water) model for seven cropping seasons during 1990 to 1996. The simulated profile soil moisture content was close to the observed data, both under optimum moisture and rainfed crop conditions, as well as when crop was sown under late (1992), early (1993) and normal (1994) conditions, with RMSE (root mean square error) values ranging between 0.62 and 1.83. The Water Stress Index (WSI), calculated using the SPAW model, had a linear, but inverse relationship with the productivity of pearl millet (y, kg ha-1). The regression equation between them was Y= -258.9 WSI + 3847.2 (R 2=0.94) and was useful for pearl millet yield estimation in the Indian arid region.